The curative effect of ethanolic extract of Moringa oleifera leaf in an animal model of liver fibrosis - Supriono; Putri, Dinda Amalia Eka; Priyanto, Tia Rahmi; Sholihah, Al Imroatus; Larasati, Putu Anissa; Nabila, Salsala Sifa; Hartaya, Arsy Hanandya; Budiarto, Andika Agus; Fachrureza, Mochamad; Wibowo, Bogi Pratomo; Mustika, Syifa (Indonesian Journal of Biomedicine and Clinical Sciences, 2024)
Studies about the prevention effect of Moringa oleifera on liver fibrosis has been reported. However, its curative effect has not been reported, yet. This study was conducted to evaluate the curative effect of M. oleifera leaf extract on liver fibrosis. It was a laboratory experimental study with a post-test-only control group design. Rats were divided into 5 groups i.e. normal control which received intraperitoneally injections of 1 mL/kg BW of 0.9% NaCl solution twice a wk for 11 wk. Liver fibrosis control which received intraperitoneally injections of 1 mL/kg BW of 10% CCl4 solution twice a wk for 11 wk. Three M. oleifera treatment group which received intraperitoneally injections of 1 mL/kg BW of 10% CCl4 solution twice a wk for 11 wk continued by M. oleifera leaf ethanolic extract at dose of 600 mg/kg BW daily for 3 (MO3), 6 (MO6), and 10 (MO10) wk, respectively. The liver fibrosis level was assessed based on the METAVIR score. Histopathological analysis of liver tissues demonstrated that the 11-week CCl4 induction successfully resulted in liver fibrosis in rats (F3 and F4). The administration of M. oleifera leaf ethanolic extract decreased METAVIR scores ranged from F3 to F1. The optimal reduction of the METAVIR scores (F1) was observed in MO3 group after 6 wk administration (p<0.05). It was indicated that M. oleifera leaf ethanolic extract ameliorated liver fibrosis. In conclusion, M. oleifera leaf ethanolic extract has a curative effect against liver fibrosis.